Novel sustainable composites prepared from cork residues and biopolymers (Biomass and Bioenergy)
Novel low-density biocomposites based on cork and two biodegradable matrices, poly(lactic acid) and poly(caprolactone), were prepared by simple melting-mixing. The surface acylation of cork was studied as a strategy to increase the compatibility with the matrices. The obtained composites were characterized in terms of thermal and mechanical properties, morphology, density and water absorption behavior. All composites showed a good dispersion of cork and a strong interfacial adhesion between the cork particles and the polymeric matrices as evidenced by SEM. The Young's modulus values of the composites were little affected for cork loads up to 10%; but for higher loadings, a considerable decrease on this parameter was observed resulting in more flexible materials. These sustainable cork based materials could find applications in several domains such as in flooring and structural applications, depending on the amount of cork and the polymeric matrix used.